2016
DOI: 10.1177/1535370216683836
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-tocopherol supplementation ameliorated hyper-inflammatory response during the early cutaneous wound healing in alloxan-induced diabetic mice

Abstract: Gamma tocopherol has shown ameliorative effect on diabetic wound healing by regulation of inflammation, oxidative stress, and apoptosis demonstrated by nuclear factor kappa B, nuclear factor (erythroid derived 2)-like 2, and sirtuin-1. AbstractDelayed wound healing is one of the major diabetic complications. During wound healing process, the early inflammatory stage is important for better prognosis. One of antioxidant nutrient, gamma-tocopherol (GT) is considered to regulate inflammatory conditions. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 70 publications
(109 reference statements)
1
29
0
Order By: Relevance
“…The evidence suggests that magnesium acts as an important cofactor for enzymes involved in protein and collagen synthesis during the process of wound curing . In addition, vitamin E intake may improve diabetic wound healing through the regulation of apoptosis, inflammatory response and oxidative stress, enhancing mitochondrial function and increasing the gene expression of cell growth factors . Joint magnesium and vitamin E supplementation may confer more beneficial effects by adding the potential influences related to their single supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence suggests that magnesium acts as an important cofactor for enzymes involved in protein and collagen synthesis during the process of wound curing . In addition, vitamin E intake may improve diabetic wound healing through the regulation of apoptosis, inflammatory response and oxidative stress, enhancing mitochondrial function and increasing the gene expression of cell growth factors . Joint magnesium and vitamin E supplementation may confer more beneficial effects by adding the potential influences related to their single supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…It is also necessary for the synthesis of protein and tissue development during wound curing process . Experimental studies proposed that vitamin E has been effective in supporting diabetic wound healing by the regulation of inflammatory reaction, apoptosis and antioxidant defense system . Considering the numerous beneficial effects of magnesium and vitamin E on mechanisms related to metabolic control, and wound healing process and due to the proposed additive action for the combination of these nutrients, the present study was conducted to evaluate the effects of magnesium and vitamin E co‐supplementation on wound healing, glycemic status, lipid profiles, and biomarkers of inflammation and oxidative stress in patients with DFU.…”
mentioning
confidence: 99%
“…or intraperitoneally (i.p.)]. Accelerated wound closure rate was detected in both genetically and chemically-induced diabetic rodents [ 51 , 52 , 53 , 54 , 55 ]. Vitamin E-related intervention facilitated the formations of new blood capillaries (angiogenesis), epithelium (epithelialization), tissue granulation, collagen fibers and dermis layers at the excisional and incisional wounds.…”
Section: Vitamin Ementioning
confidence: 99%
“…Overwhelming inflammatory response and ROS production exceeding the capacity of the endogenous defense may lead to tissue damage, thus suggesting the pivotal role of inflammation and ROS modulation during wounding [ 65 ]. Previous studies indicated that vitamin E regulated oxidative stress [decreased 4-hydroxynoneal (4-HNE) and malondialdehyde (MDA) levels] and inflammation [reduced nuclear factor kappa-light-chain-enhancer of activated B cell (NF-κB), TNF-α, and IL-1β] in diabetic cutaneous wounds [ 53 , 54 , 58 ]. Vitamin E also increased the anti-oxidative enzymes such as SOD, GPx and CAT responsible for detoxifying ROS and oxidized macromolecules in wound tissues [ 52 ].…”
Section: Vitamin Ementioning
confidence: 99%
“…For instance, gamma-tocopherol was more efficient than alpha tocopherol inhibitory prostate cancer cell expansion. This reduces oxidative DNA injury and increases superoxide dismutase activity 16 . γ tocopherol has anti inflammatory action and enhances wound healing 17 .…”
Section: Discussionmentioning
confidence: 99%